Perceived Level of Family Relationships and Predictors of Students’ Motivation from a Higher Education Institution - Erin E. Riego de Dios; Maria Isabel Guevara (Research Synergy Foundation, 2024)
Family relationships and student motivation are two crucial factors that can significantly impact student academic performance. Studies have shown that students from supportive family environments tend to have higher motivation levels and better academic performance compared to those from less supportive homes. The objective of this study is to determine the perceived level of family relationships and student motivation for a higher education institution in Olongapo City, Philippines. At the same time, the study also intends to discover the underlying predictors of student motivation. The proponents then used a descriptive correlational research design to attain the objectives. Four hundred (400) students participated voluntarily in the online survey using purposive sampling. The online poll adopted two (2) validated research instruments to analyze the perceived level of family relationships and student motivation. The garnered data underwent statistical analysis using descriptive and inferential statistics. Results reveal that the students had a high level of cohesion and a moderate degree of expressiveness and conflict in their family. There was also a high student motivation level. The study also observed significant differences in the perceived level of family relationships and students’ motivation when grouped according to their demographic characteristics. There was a weak positive association between family relationships and students’ motivation. Cohesion, expressiveness, and conflict were predictors that influenced students’ motivation to confirm relationships. This study contributes in the aspect exploring family relationship variables and how they influence a student’s learning motivation.